2000
DOI: 10.1128/jvi.74.11.4957-4966.2000
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Dengue Virus Infection in Human Cells by Alpha, Beta, and Gamma Interferons

Abstract: A role for interferon (IFN) in modulating infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
218
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(242 citation statements)
references
References 45 publications
23
218
0
1
Order By: Relevance
“…In cell culture, DENV is sensitive to type I IFN (29) (Fig. 1F), and type I and II IFN receptor-deficient mice are highly susceptible to DENV infection (22) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In cell culture, DENV is sensitive to type I IFN (29) (Fig. 1F), and type I and II IFN receptor-deficient mice are highly susceptible to DENV infection (22) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IFNs are classically known as antiviral molecules and some reports confirm that flaviviruses are susceptible to these molecules (Roers et al 1994, Diamond et al 2000. Indeed, these viruses stimulate IFN-α production (Libraty et al 2001, Deauvieau et al 2007, Palmer et al 2007, Querec et al 2009), although IFN-α induction was not compared between viruses in previous reports.…”
Section: Discussionmentioning
confidence: 96%
“…If the viruses do not grow well or form plaques, the best measuring tests are quantitative RT-PCR of viral RNA or flow cytometry of infected cells [3]. Three studies have demonstrated that dengue virus isolates vary in their capacity to infect the same cell type in vitro, depending on virus genotype and passage history [4][5][6]. The first targets of dengue virus replication, after mosquito bite, were postulated to be monocytes or macrophages and numerous studies focused on this cell lineage.…”
Section: In Vitro Modelsmentioning
confidence: 99%